2016
DOI: 10.1007/s13205-016-0467-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi response optimization for enhanced xylitol production by Debaryomyces nepalensis in bioreactor

Abstract: In this study, the optimization of different process variables-pH (4-6), aeration rate (200-550 rpm) and agitation rate (0.6-1.8 vvm) were investigated using rotating simplex method and uniform design method to enhance xylitol production from xylose by D. nepalensis in a batch stirred tank bioreactor. Maximum xylitol productivity (0.576 g L -1 h -1 ) was obtained at pH 4.0, agitation 300 rpm and aeration 1.5 vvm by rotating simplex method. Individual optimum values of pH, agitation and aeration are 4.2, 370 rp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Research works have demonstrated the great influence of the raw lignocellulosic material on the performance [231,232]. Moreover, conditions such as temperature, pH, oxygen availability and xylose concentration affect the fermentation process [233][234][235]. The presence of chemicals toxic to the microorganisms must be taken into consideration and the implementation of different detoxification processes has been analyzed [119,183].…”
Section: Xylitolmentioning
confidence: 99%
“…Research works have demonstrated the great influence of the raw lignocellulosic material on the performance [231,232]. Moreover, conditions such as temperature, pH, oxygen availability and xylose concentration affect the fermentation process [233][234][235]. The presence of chemicals toxic to the microorganisms must be taken into consideration and the implementation of different detoxification processes has been analyzed [119,183].…”
Section: Xylitolmentioning
confidence: 99%
“…For example, the bottleneck may be a consequence of the relatively low affinity of the cloned SpXYL2.2 xylitol dehydrogenase for both NAD + and xylitol (Table 4), or the intracellular pools of reduced or oxidized and NADH/NADPH ratio of co-substrates [49,50], or even the low affinity of yeast sugar permeases for xylose transport [5,14,51]. Nevertheless, the ASY-2 strain transformed with the pPGK-SaXYL1 and pTEF-SpXYL2.2 plasmids (Table 6) showed xylitol yields (Y p/s = 0.614 g xylitol/g xylose) and volumetric productivities (Q p = 0.513 g/L/h) as good as or superior to those reported by other naturally xylose fermenting yeasts [52][53][54][55] or even engineered S. cerevisiae strains [38,49,50]. It is important to note that the maximal expected theoretical yield for the biotransformation of xylose into xylitol is 0.905-0.917 g xylitol/g xylose consumed, depending on how the cells will regenerate the NADH/NADPH consumed in the reduction of xylose, and that no carbon is used for cell growth or production of other metabolites [56].…”
Section: Resultsmentioning
confidence: 93%
“…Xylitol concentration were determined using the equipped with refractive index detector and Aminex HPX-87H column (Bio-Rad, Richmond, USA) with 0.01 N H 2 SO 4 as the mobile phase running at 0.6 mL/min at 45 ºC as previously described [5]. The retention time of xylitol was 11.4 min.…”
Section: Methodsmentioning
confidence: 99%
“…The natural essential sources of xylitol are vegetables and fruits such as strawberries, yellow plum, lettuce, raspberries and cauliflower. Xylitol is used for low caloric sweetener as an appropriate sugar substitute for diabetic patients [5]. In last few years, several commercial applications of xylitol have been achieved in industries like food, dental and pharmaceuticals [6].…”
Section: Introductionmentioning
confidence: 99%